Comparative Evaluation of Phenoloxidase Activity in Different Larval Stages of Four Lepidopteran Pests After Exposure toBacillus thuringiensis - Valadéz Lira, José Alberto; Alcocer González, Juan Manuel; Damas, Gabriela; Nuñez Mejía, Gricelda; Oppert, Brenda; Rodríguez Padilla, María Cristina; Tamez Guerra, Patricia (2012)
Microbial entomopathogen–based bioinsecticides are recognized as alternatives to synthetic pesticides. Insects defend themselves against microbial pathogens by innate mechanisms, including increased phenoloxidase (PO) activity, but its relationship with microbial bioinsecticides efficacy is little known. This study evaluated the differences in PO activity at different developmental stages of the tobacco budworm Heliothis virescens Fabricius (Lepidoptera: Noctuidae), Indian meal moth Plodia interpunctella (Hübner) (Pyralidae), beet armyworm Spodoptera exigua (Hübner) (Noctuidae), and cabbage looper Trichoplusia ni (Hübner) (Noctuidae). Additionally, 2nd- and 4th-instars were exposed to the LC50 value of the commercial Bacillus thuringiensis (Bt) spray, Biobit®. The percentage of insecticidal activity (IA%) on 2nd-instar Biobit–exposed larvae was approximately the predicted 50 % mortality for all species except S. exigua. With all 4th instar Biobit–exposed larvae, mortality was not significantly different from that of unexposed larvae. Unexposed insects had a significantly higher PO activity in pre–pupae and pupae than early–instar larvae and adults, whereas PO activity was higher in adult females than in males. Correlation analysis between IA% and PO activity revealed significant r–values (p < 0.01) in 2nd instar H. virescens (r = 0.979) and P. interpunctella (r = 0.930). Second instar Biobit–exposed P. interpunctella had 10 times more PO activity than unexposed larvae. Similarly, the amount of total protein was lower in 4th instar Biobit–exposed H. virescens and higher in S. exigua. Therefore, the results indicated a relationship between Biobit susceptibility and PO activity in some cases. This information may be useful if the Biobit application period is timed for a developmental stage with low PO activity. However, more studies are needed to determine the correlation of each insect with a particular bioinsecticide.